Molding materials for carbon fiber reinforced composite materials and carbon fiber reinforced composite materials
Patent Information
- Application Number
- JP2025057749
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明によれば、不連続なリサイクル炭素繊維を用いた不織布あるいは炭素繊維マットを使用することにより環境負荷を低減できるとともに、輸送時のパッキング性および製造時の含浸性に優れ、得られる炭素繊維複合材料の曲げ弾性率に優れた炭素繊維強化複合材料用成形材料を提供すること、さらに、かかる炭素繊維強化複合材料用成形材料を用いることにより、機械特性に優れる炭素繊維強化複合材料を提供することが可能となる。
Smart Images

Figure 2026165391000001 
Figure 2026165391000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to a molding material for carbon fiber reinforced composite materials, which is suitably used for carbon fiber reinforced composite materials such as aerospace components, sporting goods, wind turbines, automobile body panels, IC trays, and general industrial components such as personal computer casings, and to a carbon fiber reinforced composite material molded using the same. [Background technology]
[0002] Carbon fiber reinforced composite materials, composed of carbon fibers and matrix resins, are used in aircraft and automobile structural materials, as well as in sports applications such as tennis rackets, golf shafts, and fishing rods, and in general industrial applications, taking advantage of their high specific strength and specific modulus. As demand for these applications expands, the disposal of carbon fiber reinforced composite materials has become one of the environmental issues. Furthermore, the production of carbon fibers is energy-intensive, generating more than twice the amount of carbon dioxide compared to aluminum.
[0003] In response to the above challenges, the development of recycling technologies for carbon fiber reinforced composite materials is being actively pursued both domestically and internationally to reduce environmental impact. Methods for recovering carbon fibers from carbon fiber reinforced composite materials include thermal decomposition, chemical decomposition, electrolytic oxidation, and mechanical pulverization. However, because the carbon fibers are cut at the stage of the raw material carbon fiber reinforced composite, it is difficult to recover continuous carbon fibers like those in virgin material. Typically, it is common to recover carbon fibers with an average fiber length ranging from the micro-order to the hundreds of millimeters order.
[0004] The aforementioned discontinuous carbon fibers can be processed and molded into a suitable molding material for carbon fiber reinforced composites according to their fiber length to obtain a carbon fiber reinforced composite material. Among the molding materials for carbon fiber reinforced composites, nonwoven fabric substrates containing discontinuous carbon fibers are a promising processing method because they can process carbon fibers of a wide range of fiber lengths. On the other hand, the nonwoven fabric form results in a bulky substrate, which leads to poor packability of the resulting carbon fiber reinforced composite molding material and reduced transport efficiency. Furthermore, due to the bulkiness of the nonwoven fabric substrate, the fiber volume content of the carbon fiber reinforced composite material does not improve, resulting in a decrease in mechanical strength.
[0005] In response to this situation, a molding material for carbon fiber reinforced composite materials containing virgin carbon short fiber webs and epoxy resin has been disclosed (Patent Document 1). Furthermore, a carbon fiber reinforced composite material containing virgin discontinuous carbon fibers with fiber lengths of 25 mm to 50 mm and epoxy resin has been disclosed (Patent Document 2). [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2023-96359 [Patent Document 2] International Publication No. 2023 / 204131 [Overview of the project] [Problems that the invention aims to solve]
[0007] The molding material for carbon fiber reinforced composite materials described in Patent Document 1 still has the problem of a significant environmental impact because virgin carbon fibers are used. Furthermore, there is no mention of the bulkiness of the base material, resulting in poor packability and low mechanical properties of the carbon fiber reinforced composite material. The carbon fiber reinforced composite material described in Patent Document 2 also still has the problem of a significant environmental impact because virgin carbon fibers are used. Furthermore, there is no mention of the bulkiness of the base material, resulting in poor packability and low specific gravity of the carbon fiber reinforced composite material, resulting in low mechanical properties.
[0008] Therefore, the present invention aims to improve upon the shortcomings of the conventional technology and provide a molding material for carbon fiber reinforced composite materials that reduces environmental impact by using a nonwoven fabric made from recycled carbon fibers, has excellent packability during transportation and impregnation during manufacturing, and produces a carbon fiber composite material with excellent flexural modulus. Furthermore, the present invention aims to provide a carbon fiber reinforced composite material with excellent mechanical properties by using such a molding material for carbon fiber reinforced composite materials. [Means for solving the problem]
[0009] To solve these problems, the molding material for carbon fiber reinforced composite materials of the present invention has the following configuration. [1] A molding material for carbon fiber reinforced composite materials comprising components (A) to (C), wherein the specific gravity of the carbon fiber reinforced composite material obtained by heating at 150°C for 2 hours under a pressurized condition of 15 MPa in a press molding machine is 1.1 or more and 1.8 or less. Component (A): Nonwoven fabric containing discontinuous recycled carbon fibers Component (B): Epoxy resin Ingredient (C): Hardener [2] A molding material for carbon fiber reinforced composite materials according to [1], wherein the number average fiber length of the recycled carbon fibers of component (A) is 2 mm or more and 90 mm or less. [3] The molding material for carbon fiber-reinforced composite materials according to [1] or [2], wherein the virgin carbon fiber that is the raw material of the recycled carbon fiber of component (A) has a tensile strength of 4.7 GPa or more and 8.0 GPa or less. [4] The viscosity at 25°C is 1.0×10 4 Pa·s or more and 1.0×10 8 Pa·s or less, the molding material for carbon fiber-reinforced composite materials according to any one of [1] to [3]. [5] The molding material for carbon fiber-reinforced composite materials according to any one of [1] to [4], wherein the fiber volume content Vfn when component (A) is pressurized at 15 MPa with a press apparatus is 20% or more and 80% or less. [6] The carbon fiber amount per unit area of component (A) is 10 g / m 2 or more and 2000 g / m 2 , the molding material for carbon fiber-reinforced composite materials according to any one of [1] to [5]. [7] The molding material for carbon fiber-reinforced composite materials according to any one of [1] to [6], comprising both an aromatic epoxy resin and an aliphatic epoxy resin as component (B). [8] The molding material for carbon fiber-reinforced composite materials according to any one of [1] to [7], wherein the viscosity of component (B) at 25°C is 0.01 Pa·s or more and 25.0 Pa·s or less. [9] A carbon fiber-reinforced composite material obtained by curing the molding material for carbon fiber-reinforced composite materials according to any one of [1] to [8]. Effects of the Invention
[0010] According to the present invention, by using a nonwoven fabric or carbon fiber mat that uses discontinuous recycled carbon fibers, it is possible to reduce the environmental load, and to provide a molding material for carbon fiber-reinforced composite materials that is excellent in packing properties during transportation and impregnation properties during production, and that gives the resulting carbon fiber composite material excellent flexural modulus. Further, by using such a molding material for carbon fiber-reinforced composite materials, it becomes possible to provide a carbon fiber-reinforced composite material having excellent mechanical properties. Modes for Carrying Out the Invention
[0011] Hereinafter, the molding material for carbon fiber reinforced composite materials and the carbon fiber reinforced composite material of the present invention will be described in detail.
[0012] The present invention is a molding material for carbon fiber reinforced composite materials comprising components (A) to (C), wherein the specific gravity of the carbon fiber reinforced composite material obtained by heating at 150°C for 2 hours under a pressurization condition of 15 MPa with a press molding machine is 1.1 or more and 1.8 or less. Component (A): A nonwoven fabric containing discontinuous recycled carbon fibers Component (B): Epoxy resin Component (C): Curing agent
[0013] In the present invention, the nonwoven fabric of component (A) refers to a form in which strands and / or monofilaments of discontinuous recycled carbon fibers are dispersed in a planar state, and examples thereof include chopped strand mats, continuous strand mats, paper-making mats, carded mats, and air-laid mats.
[0014] The method for producing the nonwoven fabric in the present invention is not particularly limited, and for example, it can be produced by dispersing carbon fibers by a dry method, a wet method, a spunbond method, a melt-blown method, an air-laid method, a scattering method or the like, and arranging them planarly. Among these, the dry method is preferable in that recycled carbon fibers with a wide range of fiber lengths can be used as the raw material. In the dry method, portability can be ensured by binding the web using a needle punch. The needle density of this needle punch is 10 needles / cm 2 or more and 2000 needles / cm 2 or less. It is preferably set to 10 needles / cm 2 or more because sufficient portability is achieved, and it is preferably 2000 needles / cm 2 or less because the packing property of the molding material for carbon fiber reinforced composite materials is improved.
[0015] In the present invention, the carbon fiber amount per unit area (hereinafter referred to as basis weight) is 10 g / m 2 or more and 2000 g / m 2Using a nonwoven fabric is preferable from the viewpoint of packability during transport. Furthermore, variations in the basis weight of the nonwoven fabric become more stable, resulting in more stable drape properties for the molding material used for carbon fiber reinforced composite materials. Reducing the number of layers during lamination is preferable from the viewpoint of workability, with a basis weight of 50g / m². 2 Furthermore, 100g / m 2 It is more preferable that the above conditions are met. Furthermore, when impregnating the molding material for carbon fiber reinforced composite materials with resin, a shorter impregnation distance is preferable, specifically 1000 g / m². 2 The following, and even 500g / m 2 The following is preferable:
[0016] In the present invention, the nonwoven fabric preferably has a fiber volume content (Vfn) of 20% to 80% when pressed at 15 MPa in a press device. A Vfn of 20% or more is preferable because it allows the mechanical properties of the carbon fiber reinforced composite material to be fully expressed. A Vfn of 80% or less is preferable because it improves the packing properties of the molding material for the carbon fiber reinforced composite material. More preferably, the Vfn is 30% to 60%.
[0017] In the present invention, the number-average fiber length of the discontinuous recycled carbon fibers constituting the nonwoven fabric is preferably 2 mm to 90 mm, more preferably 11 mm to 70 mm, and even more preferably 15 mm to 70 mm, from the viewpoint of improving the packing properties of the molding material for carbon fiber reinforced composite materials.
[0018] In this invention, recycled carbon fiber refers to carbon fiber reinforced composite material discarded as scrap material in the manufacturing process, molding material for carbon fiber reinforced composite material discarded as scrap material in the manufacturing process, or carbon fiber discarded as scrap material in the manufacturing process, and is carbon fiber recovered using recycling technology from used carbon fiber reinforced composite material or molding material for used carbon fiber reinforced composite material. The shape of the carbon fiber is not limited and examples include milled shape, chopped shape, strand shape, and woven shape.
[0019] In the present invention, the type of recycled carbon fiber is not particularly limited, and a mixture of recycled carbon fibers may be used as a raw material for the nonwoven fabric. On the other hand, recycled carbon fibers obtained from raw materials of a clearly defined type are more preferable from the viewpoint of traceability, and it is even more preferable that 90% or more of the recycled carbon fibers consist of one type. Examples of recycled carbon fibers in the present invention include polyacrylonitrile (PAN) type, pitch type, and rayon type carbon fibers. Among these, PAN type carbon fibers are preferred from the balance between the strength and elastic modulus of the carbon fiber reinforced composite material. Commercially available carbon fiber products include "Torayca®" T1100GC, "Torayca®" T1100SC, "Torayca®" T800GC, "Torayca®" T800SC, "Torayca®" T700GC, "Torayca®" T300, "Torayca®" T300B, and "Torayca®" T700SC (all manufactured by Toray Industries, Inc.), "Pyrophil®" TR50S-3L, "Pyrophil®" TR50S-6L, "Pyrophil®" TR50S-15L, "Pyrophil®" TRH50-60M, and "Pyrophil®" TRH40-50L (all manufactured by Mitsubishi Chemical Corporation).
[0020] The recycling technology used to obtain recycled carbon fibers in this invention is not particularly limited, and can include thermal decomposition, chemical decomposition, electrolytic oxidation, mechanical pulverization, etc. Considering current recycling technologies, thermal decomposition or chemical decomposition is more preferable from the viewpoint of environmental impact. Among these, chemical decomposition is particularly preferable because it can suppress the deterioration of the mechanical properties of the carbon fibers.
[0021] If the type of recycled carbon fiber is known, in order for the carbon fiber reinforced composite material to exhibit high mechanical properties, the tensile strength of the virgin carbon fiber that serves as the source of the recycled carbon fiber in this invention is preferably 4.7 GPa or more and 8.0 GPa or less, and more preferably 5.5 GPa or more and 8.0 GPa or less. A tensile strength of 4.7 GPa or more is preferable because it exhibits the high specific stiffness required for carbon fiber reinforced composite materials. A tensile strength of 8.0 GPa or less is preferable because it exhibits the high specific strength required for carbon fiber reinforced composite materials.
[0022] The tensile strength of the recycled carbon fibers in this invention may decrease from the tensile strength of the virgin carbon fibers during the recycling process described above. Therefore, since the tensile strength of the virgin carbon fibers that serve as the source of the recycled carbon fibers may not be achieved, it is more preferable that the tensile strength of the recycled carbon fibers be between 3.0 GPa and 8.0 GPa, and even more preferable that it be between 4.7 GPa and 8.0 GPa, and even more preferable that it be between 5.5 GPa and 8.0 GPa. A tensile strength of 3.0 GPa or higher is preferable because it allows for the high specific stiffness required for carbon fiber reinforced composite materials. A tensile strength of 8.0 GPa or lower is preferable because it allows for the high specific strength required for carbon fiber reinforced composite materials.
[0023] Component (B) in the present invention is an epoxy resin and is a necessary component for imparting excellent mechanical properties to the carbon fiber reinforced composite material of the present invention. Component (B) is not particularly limited as long as it is a compound containing one or more epoxy groups in one molecule. It is preferable that it contains two or more epoxy groups in one molecule because crosslinking is formed when it hardens. Furthermore, it is more preferable that it be liquid at 25°C from the viewpoint of impregnation into nonwoven fabric when manufacturing molding materials for carbon fiber reinforced composite materials. Examples of bifunctional epoxy resins containing two epoxy groups in one molecule include bisphenol A type epoxy resin, bisphenol F type epoxy resin, dicyclopentadiene type epoxy resin, or epoxy resins modified from these. Examples of polyfunctional epoxy resins containing three or more epoxy groups in a single molecule include triglycidylaminophenol-type epoxy resins, glycidylamine-type epoxy resins such as tetraglycidylamine-type epoxy resins, glycidyl ether-type epoxy resins such as tetrakis(glycidyloxyphenyl)ethane and tris(glycidyloxymethane), modified epoxy resins thereof, brominated epoxy resins obtained by brominating these epoxy resins, and aliphatic epoxy resins made from aliphatic alcohols. In addition, two or more of these epoxy resins may be used in combination as component (B). Among these, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, and bisphenol S-type epoxy resins are particularly suitable. Using these epoxy resins provides the further effect of improving the mechanical strength of carbon fiber-reinforced composite materials compared to using highly rigid epoxy resins, such as epoxy resins with a naphthalene skeleton in the molecule. This is because highly rigid epoxy resins tend to become distorted when cured quickly due to increased crosslinking density, whereas the above-mentioned epoxy resins are less likely to cause such problems.
[0024] It is more preferable to use an aromatic epoxy resin and an aliphatic epoxy resin in combination as component (B) of the present invention. This combination improves the packing properties of the molding material for carbon fiber reinforced composite materials and facilitates the development of high heat resistance in the carbon fiber reinforced composite material.
[0025] Commercially available bisphenol A type epoxy resins include "jER(registered trademark)" 825, "jER(registered trademark)" 826, "jER(registered trademark)" 827, "jER(registered trademark)" 828, "jER(registered trademark)" 834 (all manufactured by Mitsubishi Chemical Corporation), "EPICLON(registered trademark)" 850 (manufactured by DIC Corporation), "Epotote(registered trademark)" YD-128 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), "DER(registered trademark)"-331, and "DER(registered trademark)"-332 (both manufactured by Dow Chemical Company).
[0026] Commercially available bisphenol F type epoxy resins include "jER(registered trademark)" 806, "jER(registered trademark)" 807 (both manufactured by Mitsubishi Chemical Corporation), "EPICLON(registered trademark)" 830 (manufactured by DIC Corporation), and "Epotote(registered trademark)" YDF-170 (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Furthermore, commercially available alkyl-substituted tetramethylbisphenol F type epoxy resins include "Epotote(registered trademark)" YSLV-80XY (manufactured by Nippon Steel Chemical & Material Co., Ltd.).
[0027] As for aliphatic alcohols, those with 4 to 10 carbon atoms and a hydroxyl group bonded to a straight-chain or branched hydrocarbon group, and with a valent or higher hydroxyl group, are more preferable.
[0028] Examples of aliphatic alcohols with a valency of 2 or higher include 1,4-butanediol, 3-methyl-1,5-pentanediol, diethylene glycol, neopentyl glycol, 1,6-hexanediol, 1,9-nonanediol, cyclohexanedimethanol, propylene glycol, glycerin, and trimethylolpropane.
[0029] Commercially available aliphatic epoxy resins include "Denacol®" EX-321, "Denacol®" EX-313, "Denacol®" EX-314, "Denacol®" EX-411, "Denacol®" EX-412, "Denacol®" EX-512, "Denacol®" EX-521, "Denacol®" EX-612, "Denacol®" EX-614, and "Denacol®" EX-614B (all manufactured by Nagase ChemteX Co., Ltd.), "Epiol®" G-100 (manufactured by NOF Corporation), SR-GLG, SR-DGE, SR-TMP, SR-SEP, and SR-4GL (all manufactured by Sakamoto Pharmaceutical Co., Ltd.).
[0030] In the present invention, component (B) preferably has a viscosity of 0.01 Pa·s or more and 25.0 Pa·s or less at 25°C. A viscosity of 0.1 Pa·s or more is preferable because it allows for the manufacture of the molding material for carbon fiber reinforced composite materials without leakage of the epoxy resin composition from the edges. A viscosity of 25.0 Pa·s or less is preferable because it allows for sufficient impregnation of the epoxy resin composition into the nonwoven fabric during the manufacture of the molding material for carbon fiber reinforced composite materials. More preferably, the viscosity is 0.05 Pa·s or more and 5.0 Pa·s or less. Here, the viscosity of component (B) refers to the complex viscosity read at 25°C using an Anton Paar rheometer "Physica MCR501" with a 25φ parallel plate, a gap of 1 mm, vibration mode, amplitude φ=0.0025 rad, frequency of 1 Hz, and 25°C. When two or more types of epoxy resins are used as component (B), it is preferable that the viscosity at 25°C of the resin composition obtained by mixing all the components (B) used is measured and falls within the above range.
[0031] Component (C) in the invention is a component necessary to impart excellent curing properties to the molding material for carbon fiber reinforced composite materials of the present invention. Component (C) is not particularly limited as long as it can cure epoxy resin, but examples include amine-based, phenol-based, acid anhydride-based, mercaptan-based, imidazoles, tertiary amines, organophosphorus compounds, urea compounds, ammonium salts, sulfonium salts, etc. Examples of amine-based curing agents include dicyandiamide, aromatic polyamines, aliphatic amines, aminobenzoic acid esters, thiourea-added amines, and hydrazides. Examples of phenol-based curing agents include bisphenol, phenol novolac resin, cresol novolac resin, and polyphenol compounds. Examples of acid anhydride-based curing agents include phthalic anhydride, maleic anhydride, succinic anhydride, and carboxylic acid anhydrides. Examples of mercaptan-based curing agents include polymercaptan and polysulfide resin. Among the examples, amine-based curing agents are preferred. More preferably, dicyandiamide or its derivatives are preferred. Cyanidiamide readily imparts high flexural strength and heat resistance to cured resin products. Furthermore, it exhibits excellent storage stability in epoxy resin compositions. Derivatives of dicyandiamide refer to compounds obtained by combining dicyandiamide with various other compounds. Similar to dicyandiamide, these derivatives are excellent in imparting high flexural strength and heat resistance to cured resin products, and also exhibit excellent storage stability in epoxy resin compositions. Here, a derivative refers to a compound obtained by reacting dicyandiamide with various other compounds. Two or more of these compounds may be used as component (C).
[0032] Commercially available dicyandiamide products include DICY7 (manufactured by Mitsubishi Chemical Corporation), “Dicyanex®” 1400F (manufactured by Evonik Corporation), and “DYHARD®” 100 (manufactured by Alzchem K.K.).
[0033] Examples of dicyandiamide derivatives include those obtained by combining dicyandiamide with various compounds such as epoxy resins, vinyl compounds, acrylic compounds, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0034] Component (C) of the present invention is preferably present in an amount of 1 to 50 parts by mass, and more preferably 6 to 20 parts by mass, per 100 parts by mass of the total epoxy resin in the epoxy resin composition. If the epoxy curing agent content is 1 part by mass or more, a sufficient improvement in curability can be easily obtained. Furthermore, if the epoxy curing agent content is 50 parts by mass or less, the carbon fiber reinforced composite material is more likely to exhibit high heat resistance.
[0035] The heat resistance of a carbon fiber reinforced composite material obtained using the molding material for carbon fiber reinforced composite materials of the present invention can be evaluated by its glass transition temperature, which is preferably 90°C to 200°C, and more preferably 100°C to 180°C. Here, the glass transition temperature of the carbon fiber reinforced composite material is determined by measurement using a dynamic viscoelasticity analyzer (DMA). That is, a rectangular test piece cut from a resin cured plate is used to perform a DMA measurement under increasing temperature, and the temperature at which the obtained storage modulus G' inflection point is defined as the glass transition temperature.
[0036] The molding material for carbon fiber reinforced composite materials of the present invention is preferably in the form of a sheet or a zigzag pattern. From the viewpoint of transportability, a sheet shape is more preferable as it improves packability.
[0037] The basis weight of the molding material for carbon fiber reinforced composite materials is 10 g / m². 2 More than 4000g / m 2 The following is preferable: The basis weight of the molding material is 10 g / m². 2 The above is preferable because it reduces the number of layers required when molding carbon fiber reinforced composite materials, leading to improved production efficiency of fiber-reinforced composite materials. 2The following is preferable because it exhibits excellent impregnation properties of the epoxy resin composition into the reinforcing fibers when manufacturing molding materials for carbon fiber reinforced composite materials. More preferably 100 g / m 2 More than 2000 / m 2 The following applies:
[0038] The carbon fiber volume content in the molding material for carbon fiber reinforced composite materials of the present invention is 5% by mass or more and 60% by mass or less, preferably 20% by mass or less and 60% by mass or less. If the carbon fiber volume content is 5% by mass or more, the mass of the resulting fiber-reinforced composite material will not be excessive, and the advantages of fiber-reinforced composite materials, such as superior specific strength and specific modulus, can be fully realized. Furthermore, if the carbon fiber volume content is 60% by mass or less, the impregnation of the epoxy resin composition into the reinforcing fibers is excellent.
[0039] The viscosity of the carbon fiber reinforced composite molding material of the present invention at 25°C is 1.0 × 10⁻⁶. 4 Pa·s or more 1.0×10 8 It is preferable that it is less than or equal to Pa·s. 1.0 × 10 4 A Pa·s or higher is preferable because it allows for the creation of complex shapes during molding. 1.0 × 10 8 If the density is Pa·s or less, it is preferable because it can be laminated from a roll shape into a planar shape. More preferably, 1.0 × 10 5 Pa·s or more 5.0×10 7 Pa·s or less, 1.0×10 5 Pa·s or more 1.0×10 7 It is less than or equal to Pa·s.
[0040] As a method for producing the carbon fiber reinforced composite material of the present invention, an autoclave molding method and a press molding method using a molding material for carbon fiber reinforced composite materials are preferably used. In particular, the press molding method allows molding while applying high pressure to the molding material for carbon fiber reinforced composite materials, thus yielding a carbon fiber reinforced composite material with high mechanical properties.
[0041] The carbon fiber reinforced composite material of the present invention is obtained by curing the molding material for carbon fiber reinforced composite materials of the present invention, for example, by heating at 150°C for 2 hours under a pressurized condition of 15 MPa in a press molding machine. Under these conditions, the bulkiness of the nonwoven fabric used in the present invention can be sufficiently suppressed, thereby obtaining the carbon fiber reinforced composite material of the present invention with a specific gravity of 1.1 or more and 1.8 or less. A specific gravity of 1.1 or more is preferable because it exhibits the high specific strength required for carbon fiber reinforced composite materials. More preferably, the specific gravity is 1.3 or more, and even more preferably, 1.4 or more. A specific gravity of 1.8 or less is preferable because it exhibits the specific stiffness required for carbon fiber reinforced composite materials. More preferably, the specific gravity is 1.6 or less. [Examples]
[0042] The molding material for carbon fiber reinforced composite materials and the carbon fiber reinforced composite material of the present invention will be described in more detail below with reference to examples.
[0043] <Resin raw materials> The following raw materials were used to obtain the molding materials for carbon fiber reinforced composite materials in each example. In the table, the numerical values for each component in the resin composition column indicate the content, and the unit is "parts by mass" unless otherwise specified.
[0044] 1-1. Component (A): Nonwoven fabric containing recycled carbon fiber • r-T300: Recycled carbon fiber from "Torayca (registered trademark)" T300 (manufactured by Toray Industries, Inc.) (Tensile strength of virgin carbon fiber: 3.5 MPa) • r-T700: Recycled carbon fiber from "Torayca (registered trademark)" T700SC (manufactured by Toray Industries, Inc.) (Tensile strength of virgin carbon fiber: 4.9 MPa) • r-T800: Recycled carbon fiber from "Torayca (registered trademark)" T800SC (manufactured by Toray Industries, Inc.) (Tensile strength of virgin carbon fiber: 5.9 MPa) • r-T1100: Recycled carbon fiber from "Torayca (registered trademark)" T1100GC (manufactured by Toray Industries, Inc.) (Tensile strength of virgin carbon fiber: 7.0 MPa) 1-2. Nonwoven fabric made of virgin carbon fiber • v-T700: "Torayca (registered trademark)" T700SC carbon fiber (Tensile strength 4.9 MPa) manufactured by Toray Industries, Inc.
[0045] 2. Component (B): Epoxy resin • “Epotote (registered trademark)” YDF170 (manufactured by Nippon Steel Chemical & Material Co., Ltd.): Bisphenol F type epoxy resin • "Denacol®" EX-212 (manufactured by Nagase ChemteX Corporation): 1,6-Hexanediol diglycidyl ether
[0046] 3. Ingredients (C): Hardener • “jER Cure (registered trademark)” DICY7 (manufactured by Mitsubishi Chemical Corporation): Dicyandiamide
[0047] others • DCMU (manufactured by Tokyo Chemical Industry Co., Ltd.): 3-(3,4-Dichlorophenyl)-1,1-dimethylurea
[0048] (Preparation of epoxy resin composition) A resin composition was prepared by mixing each component except component (A) in the proportions listed in Tables 1 and 2.
[0049] (Production of recycled carbon fiber) • Recycled carbon fiber 1 (RC1) Recycled carbon fiber 1 (hereinafter referred to as RC1) was prepared by cutting process scraps from carbon fiber manufacturing to the lengths indicated in Tables 1 and 2, where the number-average fiber length is the same as that of the carbon fiber. The carbon fiber used for this recycled carbon fiber was the type of carbon fiber listed in component (A) of Tables 1 and 2.
[0050] • Recycled carbon fiber 2 (RC2) A carbon fiber reinforced composite material (600g) containing the carbon fiber types listed in component (A) of Tables 1 and 2 was cut to the length indicated for the number-average fiber length of the carbon fibers in Tables 1 and 2. Potassium hydroxide (100g) and N-methyl-2-pyrrolidone (5700g) were added to a 10000mL glass container, and the mixture was heated in an oil bath to 200°C for 2 hours. The resulting contents were filtered at 200°C, and the solid portion containing carbon fibers was washed with NMP and deionized water, and then dried to obtain recycled carbon fiber 2 (hereinafter, RC2).
[0051] • Recycled carbon fiber 3 (RC3) A carbon fiber reinforced composite material (600g) containing the types of carbon fibers listed in component (A) of Tables 1 and 2 was cut to the length indicated for the number-average fiber length of the carbon fibers in Tables 1 and 2. Recycled carbon fiber 3 (hereinafter referred to as RC3) was obtained by heating it to 500°C in an electric furnace in the presence of atmospheric pressure air for 3 hours.
[0052] (Production of nonwoven fabric) ·Non-woven fabric 1 (F1) The recycled carbon fibers are formed into a web sheet using a card and a cross wrapper, and then processed using a single-barb needle at a needle density of 50 needles / cm². 2 Needle punching was performed to produce nonwoven fabric 1 (hereinafter referred to as F1).
[0053] ·Non-woven fabric 2 (F2) A dispersion with a concentration of 0.1% by mass was prepared, consisting of water and a surfactant (Nacalai Tesque Co., Ltd., polyoxyethylene lauryl ether (trade name)). Carbon fiber nonwoven fabric was manufactured using this dispersion and the recycled carbon fibers. The manufacturing apparatus consists of a cylindrical container with a diameter of 1000 mm, which serves as a dispersion tank and has an opening cock at the bottom, and a linear transport section (inclination angle of 30°) connecting the dispersion tank and the papermaking tank. An agitator is attached to the opening on the top surface of the dispersion tank, allowing recycled carbon fibers and the dispersion to be introduced through the opening. The papermaking tank is equipped with a mesh conveyor with a papermaking surface of 500 mm in width at the bottom, and a conveyor capable of transporting carbon fiber nonwoven fabric is connected to the mesh conveyor. Papermaking was performed with a carbon fiber concentration of 0.05% by mass in the dispersion, and the papermaking conditions were adjusted so that the carbon fibers were dispersed in monofilament form and isotropically dispersed in the in-plane direction. The manufactured nonwoven fabric 2 (hereinafter, F2) was dried in a drying oven at 200°C for 30 minutes.
[0054] (Fabrication of molding materials for carbon fiber reinforced composite materials) Two resin films were prepared by applying the epoxy resin composition prepared in the above (Preparation of epoxy resin composition) onto a film. The nonwoven fabric prepared in the above (Preparation of nonwoven fabric) was sandwiched between the two prepared resin films and impregnated with a roller while heating at 80°C to obtain a sheet-like molding material for carbon fiber reinforced composite material. At this time, the amount of epoxy resin composition was adjusted so that the volume content of carbon fibers in the obtained molding material for carbon fiber reinforced composite material was the value shown in Tables 1 and 2.
[0055] (Fabrication of carbon fiber reinforced composite materials) Using the above-mentioned molding material for carbon fiber reinforced composite materials, the material was cured in a pressure press at 15 MPa under conditions of 150°C for 120 minutes to obtain a flat plate-shaped carbon fiber reinforced composite material measuring 300 x 400 mm x 2.0 mm.
[0056] <Rating> The evaluation for each embodiment was carried out as follows.
[0057] (Measurement of single-fiber strength of recycled carbon fiber) Using the recycled carbon fibers obtained through the above process (production of recycled carbon fibers), single-fiber strength and elongation measurements were performed in accordance with JIS R7606 (2000) under the following conditions. Furthermore, the strength (tensile strength) was calculated by dividing the maximum load on the SS curve by the single-fiber cross-section calculated from the density and basis weight. The sample size (n) was set to 5 or more. System: Tensilon Universal Tester RTI-1225 (A&D Company, Limited) • Load cell: 10N • Test speed: 1 mm / min • Sampling: 50 msec • Grip spacing: 25mm
[0058] (Measurement of the number-average fiber length of carbon fibers in nonwoven fabric) From the nonwoven fabric obtained by the above (preparation of nonwoven fabric), 400 carbon fibers were randomly extracted, and their fiber lengths were measured using an optical microscope. The number-average fiber length (Ln) calculated using the following formula was defined as the number-average fiber length of the carbon fibers. Number-average fiber length (Ln) = (ΣLi) / Nf Li: Measured fiber length (i = 1, 2, 3, ..., n) Nf: Total number of fibers measured in terms of length
[0059] (Measurement of fiber volume content of nonwoven fabric) The nonwoven fabric obtained as described above (nonwoven fabric preparation) was cut to 100 mm x 100 mm, sandwiched between two 250 mm x 250 mm x 3 mm aluminum plates, and pressed at 15 MPa using a press machine. Under pressure, the average distance between the four sides of the resulting aluminum plates was measured using calipers to obtain the average distance between the aluminum plates. This average distance between the aluminum plates is the thickness (tn) of the nonwoven fabric when pressed at 15 MPa, and the fiber volume content (Vfn) of the nonwoven fabric was measured using the following formula. Vfn = (Wn / ρf) / tn Vfn = Fiber volume content of nonwoven fabric [%] Wn = Mass of nonwoven fabric [g] Thickness of nonwoven fabric when pressurized at tn=15MPa [cm] ρf = density of carbon fiber [g / cm³]3 ]
[0060] (Evaluation of impregnation properties of molding materials for carbon fiber reinforced composite materials) When observing the central part in the thickness direction of the carbon fiber reinforced composite material molded material obtained in the above (Preparation of Molding Material for Carbon Fiber Reinforced Composite Material), if no dry fibers were observed visually, the impregnation quality was considered good (A); if there were 50 or fewer dry fibers, the impregnation quality was considered good (B); and if there were 100 or more dry fibers, the impregnation quality was considered poor (C).
[0061] (Evaluation of packing properties of molding materials for carbon fiber reinforced composite materials) When the molding material for carbon fiber reinforced composite materials obtained in the above (Preparation of molding material for carbon fiber reinforced composite materials) was wound onto a roll in a 1m width of 40kg, the case where the diameter was 80cm or less was designated as A, the case where it was 80cm or more and 150cm or less was designated as B, and the case where it was 150cm or more was designated as C.
[0062] (Evaluation of viscosity at 25°C for molding materials for carbon fiber reinforced composite materials) The molding material for carbon fiber reinforced composite materials obtained in the above (Preparation of molding material for carbon fiber reinforced composite materials) was cut into 13 mm x 47 mm pieces and laminated to a thickness of 2 mm. Dynamic viscoelasticity measurements were performed on the resulting laminate using DMA (ARES, manufactured by TA Instruments), and the viscosity (η*) value at 25°C was obtained. The measurement conditions were an angular frequency of 1.0 Hz and a strain value of 1.0%.
[0063] (Measurement of specific gravity of carbon fiber reinforced composite materials) The carbon fiber reinforced composite material obtained in the above (Preparation of Carbon Fiber Reinforced Composite Material) was cut into 150 mm x 1000 mm sections, the cut surfaces were covered with tape, and the fiber volume content was measured using the water displacement method. The measurement of fiber volume content using the water displacement method was performed in accordance with JIS K7052.
[0064] (Measurement of the flexural modulus of carbon fiber reinforced composite materials) The bending strength of the carbon fiber reinforced composite material obtained in the above (Preparation of Carbon Fiber Reinforced Composite Material) was measured in accordance with JIS K7074:1988. Test specimens cut to a width of 15 mm and a length of 100 mm were measured using an Instron universal testing machine (manufactured by Instron) by a three-point bending test. The measurement was performed with a crosshead speed of 5 mm / min, a span of 80 mm, a thickness of 5 mm, and a support diameter of 2 mm, and the bending modulus was determined. The bending modulus was calculated as the average of five samples.
[0065] (Evaluation of the environmental impact of carbon fiber reinforced composite materials) The carbon dioxide emissions per kilogram (Cv) were calculated by multiplying the carbon dioxide emissions per kilogram per kilogram of each raw material listed in Tables 1 and 2 by the mass ratio of each raw material in the carbon fiber reinforced composite material listed in Tables 1 and 2. Furthermore, the carbon dioxide emissions per kilogram (Cr) were calculated by replacing the value of component (A) used in the calculation of Cv with the carbon dioxide emissions per kilogram per kilogram per kilogram of recycled carbon fiber listed in Tables 1 and 2. The environmental load rate (Ep) was calculated using the following formula: When the total carbon dioxide emissions per kilogram of the carbon fiber reinforced composite material were divided by 100, a result of 90% or more and 100% or less was defined as C, a result of 60% or less and less than 90% was defined as B, and a result of 0% or more and less than 60% was defined as A. Ep = Cr / Cv * 100
[0066] (Evaluation of heat resistance of carbon fiber reinforced composite materials) After demolding the carbon fiber reinforced composite material obtained in the above (fabrication of carbon fiber reinforced composite material) and confirming that the temperature had decreased to 25°C, the material was placed on a flat surface at 25°C. If there was significant warping, it was classified as C; if there was slight warping, it was classified as B; and if there was almost no warping, it was classified as A.
[0067] (Examples 1-19) Recycled carbon fibers were prepared as described above (Preparation of Recycled Carbon Fibers) using the types and mass parts of each component listed in Tables 1 and 2. The obtained recycled carbon fibers were measured as described above (Measurement of Single Yarn Strength of Recycled Carbon Fibers), and the results are shown in Tables 1 and 2. Nonwoven fabrics were prepared using the manufacturing methods and basis weights described in Tables 1 and 2, as described in (Preparation of Nonwoven Fabrics) above. The obtained nonwoven fabrics were measured as described in (Measurement of Number-Average Fiber Length of Carbon Fibers in Nonwoven Fabrics) and (Measurement of Fiber Volume Content of Nonwoven Fabrics) above, and the results are shown in Tables 1 and 2. Using the carbon fiber volume content and basis weight listed in Tables 1 and 2, molding materials for carbon fiber reinforced composite materials were prepared as described above (Preparation of molding materials for carbon fiber reinforced composite materials). The obtained molding materials for carbon fiber reinforced composite materials were measured as described above (Evaluation of impregnation properties of molding materials for carbon fiber reinforced composite materials), (Evaluation of packing properties of molding materials for carbon fiber reinforced composite materials), and (Evaluation of viscosity of molding materials at 25°C for carbon fiber reinforced composite materials), and the results were favorable as shown in Tables 1 and 2. As described above (Preparation of carbon fiber reinforced composite material), a carbon fiber reinforced composite material was prepared. The specific gravities of the obtained carbon fiber reinforced composite material were obtained as described above (Measurement of specific gravity of carbon fiber reinforced composite material), as shown in Tables 1 and 2. The obtained carbon fiber reinforced composite material was measured as described above (Measurement of flexural modulus of carbon fiber reinforced composite material), (Evaluation of environmental load of carbon fiber reinforced composite material), and (Evaluation of heat resistance of carbon fiber reinforced composite material), and the results were good as shown in Tables 1 and 2.
[0068] (Comparative Example 1) An epoxy resin composition was prepared as described above (Preparation of epoxy resin composition) using the types and mass parts of each component listed in Table 2. The virgin carbon fibers listed in Table 2 were replaced with virgin carbon fibers in the above (Measurement of single-fiber strength of recycled carbon fibers) and measured, as shown in Table 2. Using the manufacturing method and basis weight described in Table 2, the recycled carbon fibers described above (for nonwoven fabric production) were replaced with virgin carbon fibers to produce a nonwoven fabric. The obtained nonwoven fabric was measured as described above (for the number-average fiber length of carbon fibers in the nonwoven fabric) and (for the fiber volume content of the nonwoven fabric), and the results are shown in Table 2. Using the carbon fiber volume content and basis weight listed in Table 2, molding materials for carbon fiber reinforced composite materials were prepared as described above (Preparation of molding materials for carbon fiber reinforced composite materials). The obtained molding materials for carbon fiber reinforced composite materials were measured as described above (Evaluation of impregnation properties of molding materials for carbon fiber reinforced composite materials), (Evaluation of packing properties of molding materials for carbon fiber reinforced composite materials), and (Evaluation of viscosity of molding materials at 25°C for carbon fiber reinforced composite materials), and the results were favorable as shown in Table 2. As described above (Preparation of carbon fiber reinforced composite material), a carbon fiber reinforced composite material was prepared. The specific gravity of the obtained carbon fiber reinforced composite material was obtained as shown in Table 2, as described above (Measurement of specific gravity of carbon fiber reinforced composite material). The obtained carbon fiber reinforced composite material was measured as described above (Measurement of flexural modulus of carbon fiber reinforced composite material), (Evaluation of environmental load of carbon fiber reinforced composite material), and (Evaluation of heat resistance of carbon fiber reinforced composite material), and the evaluation of the environmental load was poor, rated as C.
[0069] (Comparative Example 2) An epoxy resin composition was prepared as described above (Preparation of epoxy resin composition) using the types and mass parts of each component listed in Table 2. The virgin carbon fibers listed in Table 2 were replaced with virgin carbon fibers in the above (Measurement of single-fiber strength of recycled carbon fibers) and measured, as shown in Table 2. Using the manufacturing method and basis weight described in Table 2, the recycled carbon fibers described above (for nonwoven fabric production) were replaced with virgin carbon fibers to produce a nonwoven fabric. The obtained nonwoven fabric was measured as described above (for the number-average fiber length of carbon fibers in the nonwoven fabric) and (for the fiber volume content of the nonwoven fabric), and the results are shown in Table 2. Using the carbon fiber volume content and basis weight listed in Table 2, molding materials for carbon fiber reinforced composite materials were prepared as described above (Preparation of molding materials for carbon fiber reinforced composite materials). The obtained molding materials for carbon fiber reinforced composite materials were measured as described above (Evaluation of impregnation properties of molding materials for carbon fiber reinforced composite materials), (Evaluation of packing properties of molding materials for carbon fiber reinforced composite materials), and (Evaluation of viscosity of molding materials at 25°C for carbon fiber reinforced composite materials), and the results were favorable as shown in Table 2. As described above (Preparation of carbon fiber reinforced composite material), a carbon fiber reinforced composite material was prepared. The specific gravity of the obtained carbon fiber reinforced composite material was obtained as shown in Table 2, as described above (Measurement of specific gravity of carbon fiber reinforced composite material). The obtained carbon fiber reinforced composite material was measured as described above (Measurement of flexural modulus of carbon fiber reinforced composite material), (Evaluation of environmental load of carbon fiber reinforced composite material), and (Evaluation of heat resistance of carbon fiber reinforced composite material). The environmental load and heat resistance evaluations were both rated as C, which is unsatisfactory.
[0070] (Comparative Example 3) Recycled carbon fibers were prepared using the types and mass parts of each component listed in Table 2, as described above (Preparation of Recycled Carbon Fibers). The obtained recycled carbon fibers were measured as described above (Measurement of Single Yarn Strength of Recycled Carbon Fibers), and the results are shown in Table 2. Nonwoven fabrics were prepared using the manufacturing method and basis weight described in Table 2, as described in (Preparation of Nonwoven Fabrics) above. The obtained nonwoven fabrics were measured as described in (Measurement of Number-Average Fiber Length of Carbon Fibers in Nonwoven Fabrics) and (Measurement of Fiber Volume Content of Nonwoven Fabrics) above, and the results are shown in Table 2. Using the carbon fiber volume content and basis weight listed in Table 2, a molding material for carbon fiber reinforced composite materials was prepared as described above (Preparation of molding material for carbon fiber reinforced composite materials). The obtained molding material for carbon fiber reinforced composite materials was measured as described above (Evaluation of impregnation properties of molding material for carbon fiber reinforced composite materials), (Evaluation of packing properties of molding material for carbon fiber reinforced composite materials), and (Evaluation of viscosity of molding material at 25°C of carbon fiber reinforced composite materials). As shown in Table 2, the packing properties were poor. As described above (Preparation of carbon fiber reinforced composite material), a carbon fiber reinforced composite material was prepared. The specific gravity of the obtained carbon fiber reinforced composite material was obtained as shown in Table 2, as described above (Measurement of specific gravity of carbon fiber reinforced composite material). The obtained carbon fiber reinforced composite material was measured as described above (Measurement of flexural modulus of carbon fiber reinforced composite material), (Evaluation of environmental load of carbon fiber reinforced composite material), and (Evaluation of heat resistance of carbon fiber reinforced composite material). The environmental load was found to be poor (C), and the flexural modulus was found to be poor (5 GPa).
[0071] (Comparative Example 4) Recycled carbon fibers were prepared using the types and mass parts of each component listed in Table 2, as described above (Preparation of Recycled Carbon Fibers). The obtained recycled carbon fibers were measured as described above (Measurement of Single Yarn Strength of Recycled Carbon Fibers), and the results are shown in Table 2. Nonwoven fabrics were prepared using the manufacturing method and basis weight described in Table 2, as described in (Preparation of Nonwoven Fabrics) above. The obtained nonwoven fabrics were measured as described in (Measurement of Number-Average Fiber Length of Carbon Fibers in Nonwoven Fabrics) and (Measurement of Fiber Volume Content of Nonwoven Fabrics) above, and the results are shown in Table 2. Using the carbon fiber volume content and basis weight listed in Table 2, a molding material for carbon fiber reinforced composite materials was prepared as described above (Preparation of molding material for carbon fiber reinforced composite materials). The obtained molding material for carbon fiber reinforced composite materials was measured as described above (Evaluation of impregnation properties of molding material for carbon fiber reinforced composite materials), (Evaluation of packing properties of molding material for carbon fiber reinforced composite materials), and (Evaluation of viscosity of molding material at 25°C of carbon fiber reinforced composite materials). As shown in Table 2, the packing properties were poor. As described above (Preparation of carbon fiber reinforced composite material), a carbon fiber reinforced composite material was prepared. The specific gravity of the obtained carbon fiber reinforced composite material was obtained as shown in Table 2, as described above (Measurement of specific gravity of carbon fiber reinforced composite material). The obtained carbon fiber reinforced composite material was measured as described above (Measurement of flexural modulus of carbon fiber reinforced composite material), (Evaluation of environmental load of carbon fiber reinforced composite material), and (Evaluation of heat resistance of carbon fiber reinforced composite material). The environmental load was found to be poor (C), and the flexural modulus was found to be poor (3 GPa).
[0072] Table 1
[0073] Table 2
Claims
1. A molding material for carbon fiber reinforced composite materials comprising components (A) to (C), wherein the specific gravity of the carbon fiber reinforced composite material obtained by heating at 150°C for 2 hours under a pressurized condition of 15 MPa in a press molding machine is 1.1 or more and 1.8 or less. Component (A): Nonwoven fabric containing discontinuous recycled carbon fibers Component (B): Epoxy resin Ingredient (C): Hardener
2. The molding material for carbon fiber reinforced composite materials according to claim 1, wherein the number average fiber length of the recycled carbon fibers of component (A) is 2 mm or more and 90 mm or less.
3. A molding material for carbon fiber reinforced composite materials according to claim 1 or 2, wherein the virgin carbon fiber that serves as the source for the recycled carbon fiber of component (A) has a tensile strength of 4.7 GPa or more and 8.0 GPa or less.
4. The viscosity at 25°C is 1.0 × 10⁻⁶. 4 Pa・s or more 1.0×10 8 A molding material for carbon fiber reinforced composite materials according to claim 1 or 2, wherein the Pa·s is less than or equal to Pa·s.
5. A molding material for carbon fiber reinforced composite materials according to claim 1 or 2, wherein the fiber volume content Vfn when component (A) is pressurized at 15 MPa in a press device is 20% or more and 80% or less.
6. The amount of carbon fiber per unit area of component (A) is 10 g / m². 2 More than 2000g / m 2 A molding material for carbon fiber reinforced composite materials according to claim 1 or 2.
7. A molding material for carbon fiber reinforced composite materials according to claim 1 or 2, comprising both an aromatic epoxy resin and an aliphatic epoxy resin as component (B).
8. A molding material for carbon fiber reinforced composite materials according to claim 1 or 2, wherein the viscosity of component (B) at 25°C is 0.01 Pa·s or more and 25.0 Pa·s or less.
9. A carbon fiber reinforced composite material obtained by curing the molding material for carbon fiber reinforced composite materials according to claim 1 or 2.
Citation Information
Patent Citations
Molding material for carbon fiber-reinforced composite material, and carbon fiber-reinforced composite material
JP2023096359A
Fiber-reinforced resin molded body and method for producing same
WO2023204131A1